Effect of Crop Establishment Method and Fertilizer Management on Yield Performance of Boro Rice (Var. Brri DHAN28) In T. Aman-Mustard-Boro Rice Cropping Pattern (Bangladesh Agronomy Journal, 2023)
The Study was carried out at the Salpoborian village under Sadr papilla of Mymensingh from February to June 2014 to assess the effect of crop establishment method and fertilizer management on the yield performance of Boro rice (var. BRRI dhan28) in T. Aman-Mustard-Boro rice cropping pattern. The experiment comprised three crop establishment methods viz. traditional puddled-transplanting (TPT), unpuddled-one pass in dry condition (UDC), unpuddled-zero tillage (UZT) and five levels of fertilizers viz., 100-60-40-60-10 N-P-K-S-Zn kg ha-1 at recommended (RD) dose (F1), N-K-S-Zn at RD plus 50% P (F2), N-P-S-Zn at RD plus 50% K (F3), P-K-S-Zn at RD plus 75% N as Guti urea (2.7 g/4 hills) (F4), P-K-S-Zn at RD plus 75% N as pilled urea (F5). The experiment was laid out in a split -plot design with 4 replications with crop establishment method in the main- plots and fertilizer management in the sub-plots. Grain yield was not significantly influenced by crop establishment method, fertilizer management and their interactions. However, numerically the maximum grain yield of  3.19 t ha−1  was found in both unpuddled-one pass in dry condition (UDC) and unpuddled-zero tillage (UZT) with  3.32 t ha−1 in P-K-S-Zn at RD plus 75% N as pilled urea (F5) and 3.47 t ha−1 in unpuddled-one pass in dry condition with P-K-S-Zn at RD plus 75% N as pilled urea and traditional puddled-transplanting with P-K-S-Zn at RD plus 75% N as pilled urea. Similar higher gross margin (Tk. 26629 and Tk. 27428) and benefit cost ratio (1.61 and 1.60) was also observed in UZT × F4 and UDC × F5, respectively. So, it can be concluded that unpuddled-zero tillage with P-K-S-Zn at RD plus 75% N as Guti urea (UZT × F4) and unpuddled-one pass in dry condition with P-K-S-Zn at RD plus 75% N as prilled urea (UDC × F5) is the beneficial technique for Boro rice (var. BRRI dhan28) cultivation in T. Aman-Mustard-Boro rice cropping pattern.Bangladesh Agron. J. 2023, 26(1): 32-39